ESTUDANTES OU OUVINTES? O PÚBLICO DAS FACULDADES DE LETRAS E CIÊNCIAS NO SÉCULO 19 (1808-1878) - Boris Noguès (Associação Sul-Rio-Grandense de Pesquisadores em História da Educação (ASPHE), 2011)
This study contrasts two categories of people within the audience of the faculties of Letters and Sciences in the 19th century: the pupils, who sought training, and the listeners, for whom attending the lectures was above all a leisure activity. The decrees organizing the Imperial University, in 1808, provided courses for students. But during the Restoration (1815-1830), the faculty courses became places of political expression, social representation or, more simply, entertainment and culture for the French high society who had time to waste. In Letters particularly, a course was a spectacle without a scientific program or training goals. The value of the teacher was measured in terms of its rhetorical qualities, rather than its scientific capabilities. Yet from 1837 onwards, criticism could be heard against this trend. It pointed to the inability of such a system to properly train scientists and they were based on comparison with practices abroad (London and Turin were quoted in 1840, before the German model became the reference in the 1860s). If the government did not respond immediately, teaching practices partly filled the deficiencies, through the establishment of closed conferences or private lessons, held at the personal initiative of a particular teacher. The official reorientation of the courses was done gradually, starting in 1855 for political reasons (focus education on science contents prevented faculties from becoming places of contestation) and economic reasons (industrialized France needed managerial staff). In 1868, the Ecole Pratique des Hautes Etudes was created after the German model; it was open only to selected students and repulsed the public outside. After the 1870 defeat against Germany and the establishment of the Republic, the Government required teachers to provide effective training in their courses and generalized to all students enrolled lectures and tutorials reserved for them.